Pulmonary function in healthy young adult Indians in Madras. Issue 8 (August 1990) - Vijayan, V K; Kuppurao, K V; Venkatesan, P; Sankaran, K; Prabhakar, R
Abstract : Forced vital capacity, forced expiratory volume in one second, functional residual capacity, residual volume, total lung capacity, and single breath diffusing capacity measurements (effective alveolar volume, carbon monoxide transfer factor, and transfer coefficient) were measured in 247 young healthy adults (130 male, 117 female) aged 15-40 years living in Madras. Subjects were of Dravidian stock, living at sea level with rice as their staple diet. Regression equations were derived for men and women for predicting normal pulmonary function for young adults in South India. The values were similar to those reported for subjects from Western India and lower than those reported for North Indians and caucasians.